Correlation of clinical and radiological outcome of distal radius fractures treated with volar plating - Gowda, Rajath H. P.; Daddimani, Ravi M.; Madhava Murthy, Srinath K. (International Journal of Research in Orthopaedics, 2021)
Background: Distal radius fractures are one of the most common injuries treated by an orthopaedic surgeon, accounting for approximately one sixth of all fractures. Due to increase in incidence of high velocity trauma, the injury is seen occurring in young patients more often. A displaced fracture deranges the wrist anatomy causing deformity and loss of function at the wrist joint. Open reduction and internal fixation with plate using a volar approach allows anatomical reduction of the fracture, stable fixation aiding in early mobilization. Methods: Our study was a hospital-based study conducted during the period June 2016 to November 2018. A total of 30 patients with distal radius fracture were treated with ORIF with a volar plate. They were followed up for a year and clinical and radiological outcomes were evaluated. Results: Among the 30 patients studied 25 were males and 5 were females with mean age of 36.23 years. According to Gartland and Werley demerit scoring system, 15 of them had excellent result at the end of one year. 13 Of them had good and 2 of them had fair results. Radiological assessment was done by Sarmiento’s modification of the Lind storm criteria and 15 of them had excellent results. 15 patients had good radiological outcome. Conclusions: From this study we conclude that ORIF with volar plating can provide good clinical and functional outcome in distal radius fractures. Anatomical reduction of the fracture fragments is the key in achieving good results.